Caught in the cross-fire ; Balancing in a string ; Mitch [videorecording] - Lazaro, Cheche (The Probe Team, 1989)
Talks about the military operations against the in Negros killing many civilians in the crossfire ; poverty alleviation and inflation ; and the link of Alma Vaca, Maya Valdez and Mitch Valdez.